Evaluasi Penggunaan Antibiotik pada Pasien Anak Rawat Inap di RSD Dr. Soebandi Jember: Evaluation of Antibiotic Use For Pediatric at RSD Dr. Soebandi Jember - Rachmawati, Sinta; Masito, Dewi Khurmi; Rachmawati, Ema (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2020)
Infection is one of the health problems. It is mostly caused by bacteria. The increased incidence of bacterial infection results in higher antibiotic use. It can lead to antibiotic resistance risk. Antibiotic resistance may occur in pediatric patients. Morbidity, mortality, and high cost of medication are impact of this condition. Evaluation of antibiotic use needs to be done to ensure responsible use of antibiotics. ATCD/DDD (Anatomical Therapeutic Chemical/ Defined Daily Dose) method can be used to evaluate antibiotic use quantitatively. ATC classification is a system of grouping active substances according to their location of action and DDD is a measurement system that is connected to the ATC code.The purpose of this study was determining the profile of antibiotic use and measuring quantitative evaluation with ATC/DDD method in pediatric patients. The data was collected by observing the hospital medical record. The results of this study showed that cephalosporin (46,22%) was the most used group and cefotaxime (31,15%) was the most used type of antibiotic. While, the quantitative evaluation with ATC/DDD method indicated that the highest of antibiotic use was ceftriaxone (11,30 DDD/100 patient days) and the lowest was amikacin (0,03 DDD/100 patient days).